Occurrence of antiparasitic pesticides in sediments near salmon farms in the northern Chilean Patagonia. (15th February 2017) - Tucca, Felipe; Moya, Heriberto; Pozo, Karla; Borghini, Francesca; Focardi, Silvano; Barra, Ricardo
Abstract: Growth of the aquaculture industry has triggered the need for research into the potential environmental impact of chemicals used by salmon farms to control diseases. In this study, the antiparasitic pesticides emamectin benzoate (EB), diflubenzuron (DI), teflubenzuron (TE), and cypermethrin (CP) were measured in sediments near salmon cages in southern Chile. Concentrations for EB were between 2.2 and 14.6 ng g − 1, while the benzoylphenyl ureas DI and TE were detected in the ranges of 0.1 to 1.2 ng g − 1 and 0.8 to 123.3 ng g − 1, respectively. These results were similar to data reported for the Northern Hemisphere. On the other hand, the pyrethroid CP was detected in higher concentrations, ranging from 18.0 to 1323.7 ng g − 1 . According to reported toxicity data, this range represents a potential risk for benthic invertebrates. This report is the first baseline attempt at assessing antiparasitic pesticide levels in the Chilean Patagonia. Highlights: Antiparasitic pesticides were detected in sediments at different sites near salmon farms in northern Patagonia. Benzoylphenyl ureas concentrations were lower than their observed values at northern hemisphere salmon farms. Cypermethrin levels in southern Chile appear to represent a risk to local benthic organisms.